Toward Business Model Innovation in Digital Servitization: The Interplay Between Digitalization and Sustainability - Abeysinghe, Odara; Abed Alghani, Khaled (Palgrave Macmillan, 2026)
In the digital transformation era, firms are increasingly adopting servitization strategies with advanced technologies to enhance customer value and achieve sustainability. This transition from traditional product-centric to digital servitization models (i.e., product-service systems) emphasizes a paradigm shift that requires innovation in business models and organizational architectures to fulfill emerging needs of digitalization and sustainability. However, shifting toward digital servitization is a complex organizational change process that ultimately extends value propositions, creates new value and delivery systems while generating revenue. As it appears, an effective integration of digitalization and sustainability plays a crucial role in this transition process, ultimately steering business model innovation. Thus, this book chapter explores the dynamic relationship between digitalization and sustainability and how it reconfigures service business models from a business model innovation perspective. The findings reveal that integrating digitalization and sustainability is not linear but necessitates strategy formation where firms can develop outcome-based business models with the emphasis of environmental value, build internal capabilities and culture of continuous improvement, adopt customer-oriented value and collaborate with ecosystem actors in co-creation to achieve sustainable outcomes. This is a
Keywords: Digital servitization; Sustainability; Value logic; Business model innovation; fi=Strateginen johtaminen|en=Strategic Management|; fi=Strateginen johtaminen|en=Strategic Management|